Pterin-6-aldehyde, Xanthine Oxidase Inhibitor and Superoxide Scavenger, Directly React with Peroxynitrite - Mori Hiroko; Arai Toshiyuki; Ishii Hisanari; Endo Nobuyuki; Suzuki Toshinori; Fukudal Kazuhiko (Pteridines, 1999)
The effect of pterin-6-aldehyde (P6A), xanthine oxidase inhibitor and superoxide scavenger, on the production of nitrotyrosine as a footprint of tyrosine nitration by peroxynitrite, was compared with that of uric acid, a peroxynitrite scavenger. The amounts of tyrosine, P6A and nitrotyrosine were quantified using reversed-phase high-performance liquid chromato-graphy (RP-HPLC). P6A suppressed nitrotyrosine formation less effectively than uric acid, that is, 0.25 mM P6A reduced nitrotyrosine formation to 67.9± 10.8%, while 0.025 mM uric acid reduced it to 34.2± 1.6%. In living systems, peroxynitrite is generated by the reaction of super-oxide with nitric oxide and has a variety of toxic effects. Our results show that P6A is not necessarily a strong scavenger of peroxynitrite. However, since P6A is a potent scavenger of superoxide, P6A is thought to totally suppress peroxynitrite generation. Compounds that scavenge both superoxide and peroxynitrite may be useful in tissue damage in which reactive oxygen species are involved.